Journal of translational medicine reviewer acknowledgement 2012 - Marincola, Francesco (BioMed Central, 2013)
CONTRIBUTING REVIEWERS: The editor of Journal of Translational Medicine would like to thank all our reviewers who have contributed to the journal in Volume 10 (2012).